2014
DOI: 10.1111/jopy.12092
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Motive-Trait Interaction on Satisfaction of the Implicit Need for Affiliation Among German and Cameroonian Adults

Abstract: Research provided evidence that personality traits influence the realization of implicit motives: Extraversion supported the successful realization of the implicit motives for affiliation and power, whereas introversion deflected implicit motives away from significant goals and created difficulties in goal attainment. Based on those findings on motive-trait interaction, we tested whether the traits of Neuroticism, Agreeableness, and Extraversion affect the satisfaction of the implicit affiliation motive (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…For example, Winter et al (1998) suggest that extraverts might attend parties (i.e., personality-behavior link) to fulfill affiliative motives (i.e., human motive-goal link), whereas introverts may do so (personality-behavior link) to pursue other goals, such as networking for a job (i.e., human motive-goal link). This and other research (e.g., Chen et al, 2015;Hofer et al, 2015) indicates that human motives and personality traits connect to different levels or aspects of a person that may conjointly shape that person's thoughts and feelings, interactively predicting the person's behavior over the course of many years. Hence, next to personality traits, human motives may add to the understanding of the individual roots of PSM.…”
Section: Theory Explicit and Implicit Motivessupporting
confidence: 51%
“…For example, Winter et al (1998) suggest that extraverts might attend parties (i.e., personality-behavior link) to fulfill affiliative motives (i.e., human motive-goal link), whereas introverts may do so (personality-behavior link) to pursue other goals, such as networking for a job (i.e., human motive-goal link). This and other research (e.g., Chen et al, 2015;Hofer et al, 2015) indicates that human motives and personality traits connect to different levels or aspects of a person that may conjointly shape that person's thoughts and feelings, interactively predicting the person's behavior over the course of many years. Hence, next to personality traits, human motives may add to the understanding of the individual roots of PSM.…”
Section: Theory Explicit and Implicit Motivessupporting
confidence: 51%
“…A closer look at the theory of needs reveals that need for achievement, for instance, is a psychological characteristic and is in line with the definition of a personality trait by Ajzen (2005). Moreover, the research provided evidence that personality traits influence the realization of implicit motives (Hofer et al 2015). Internal factors, such as personality traits and the individual structure of needs, as well as external factors (social norms and cultural characteristics), may result in different motives for behavior and performance.…”
Section: Clarification and Organization Of The Concept Entrepreneuriamentioning
confidence: 95%
“…Accordingly, affiliation-motivated leaders might only be successful, if they are also extraverted. As Hofer et al (2015) rather found neuroticism to constrain and agreeableness to support the expression of nAff, research needs to disentangle how the Big Five act on the expression of motives and modulate their association with effective leadership.…”
Section: Limitations and Future Researchmentioning
confidence: 99%